Using Heartfulness Meditation and Brainwave Entrainment to Improve Teenage Mental Wellbeing - Yadav, Ghazal Suhani; Cidral-Filho, Francisco José; Iyer, Ranjani B. (Frontiers in Psychology, 2021)
Teenagers are highly susceptible to mental health issues and this problem has been exacerbated by the quarantine restrictions of COVID-19. This study evaluated the use of Heartfulness Meditation and Audio Brainwave Entrainment to help teenagers cope with mental health issues. It used 30-min Heartfulness meditation and 15-min brainwave entrainment sessions with binaural beats and isochronic tones three times a week for 4 weeks. Using a pretest-posttest methodology, participants were asked to complete a survey battery including the Pittsburgh Quality of Sleep Index, Perceived Stress Scale, Patient Health Question-9, Profile of Mood States, and Cambridge Brain Health assessment. Participants (n = 40) were divided into four experimental groups: the control group (n = 9), Audio Brainwave Entrainment group (n = 9), Heartfulness Meditation group (n = 10), and a combined group (n = 12), for a 4-week intervention. Data were analyzed with paired t-tests. The singular Audio Brainwave Entrainment group did not see statistically significant improvements, nor did any of the intervention groups for brain health (p > 0.05). This study, however, proved the efficacy of a 4-week Heartfulness Meditation program to regulate overall mood (p = 0.00132), stress levels (p = 0.0089), state depression (POMS; p = 0.0037), and anger (p = 0.002). Results also suggest adding Audio Brainwave Entrainment to Heartfulness Meditation may improve sleep quality (p = 0.0377) and stress levels (p = 0.00016).